VARIED CLINICAL PRESENTATIONS OF CHANCROID: A CASE SERIES AND LITERATURE REVIEW - SPANDAN K. SHAH; KRUNAL TRALSAWALA; DHARA D. PATEL; SOM J LAKHANI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study aimed to explore the diverse clinical manifestations of chancroid, investigate associated coinfections, and evaluate treatment outcomes. Methods: A prospective case series was conducted involving six patients diagnosed with chancroid. Each patient underwent a detailed clinical evaluation, with photographic documentation of lesions. Laboratory investigations were performed to confirm chancroid and identify potential coinfections. Treatment was tailored according to the clinical findings and diagnostic results. Results: The study revealed a spectrum of atypical ulcer presentations, including phagedenic ulcers, large ulcers, and small discrete lesions, suggesting the influence of coexisting STIs. Laboratory evaluations confirmed the presence of coinfections such as HIV, syphilis, and herpes in several cases. Conclusion: Chancroid can present with diverse and atypical clinical features, often in the context of coexisting STIs. Early diagnosis and appropriate management are critical to preventing complications and improving patient outcomes.